Modelling Factors Affecting Students’ And Instructors’ Behavior And Engagement In The Online Environment Using Educational Data Mining And Dematel Technique - Aldowah, Hanan Ahmad Yahya (2023)
The first aim of this study is to investigate the use of LMS by students and instructors to evaluate their online activities, discover user behavior and engagement patterns, and to obtain some indicators to better understand their level of engagement. For this purpose, statistical, visualization, and clustering Educational Data Mining techniques are used to analyze the courses conducted through hybrid and fully online learning modes offered in four semesters at the Universiti Sains Malaysia.